Effects of Environmental Factors on Nutrients Release at Sediment-Water Interface and Assessment of Trophic Status for a Typical Shallow Lake, Northwest China - Dekun Hou; Jiang He; Changwei Lü; Ying Sun; Fujin Zhang; Khureldavaa Otgonbayar (The Scientific World Journal)
Surface sediment and water samples were collected from Daihai Lake to study the biogeochemical characteristics of nitrogen and phosphorus, to estimate the loads of these nutrients, and to assess their effects on water quality. The contents and spatial distributions of total phosphorus (TP), total nitrogen (TN), and different nitrogen forms in sediments were analyzed. The results showed that concentrations of TN and TP in surface sediments ranged from 0.27 to 1.78 g/kg and from 558.31 to 891.29 mg/kg, respectively. Ratios of C : N ranged between 8.2 and 12.1, which indicated that nitrogen accumulated came mainly from terrestrial source. Ratios of N : P in all sampling sites were below 10, which indicated that N was the limiting nutrient for algal growth in this lake. Effects of environment factors on the release of nitrogen and phosphorus in lake sediments were also determined; high pH values could encourage the release of nitrogen and phosphorus. Modified Carlson’s trophic state index (TSIM) and comprehensive trophic state index (TSIC) were applied to ascertain the trophic classification of the studied lake, and the values of TSIM and TSIC ranged from 53.72 to 70.61 and from 47.73 to 53.67, respectively, which indicated that the Daihai Lake was in the stage of hypereutropher.